Consolidate The Constitutional Monarchy in The Kurdistan Regionfirst - Wzhar Fahri Saadi; Hawar Muhammed Yousif; Kareem Kawa Kareem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
A constitutional monarchy, parliamentary monarchy, or democratic monarchy, is a form of monarchy in which the king exercises his power according to a constitution and is not alone in making decisions. Constitutional monarchies differ from absolute monarchies in that they are obliged to exercise power within limits defined by an established legal framework. In the transition to democracy, some autocracies changed to republics while others evolved into constitutional monarchies, a constitutional monarch in a parliamentary democracy, the head of state is a hereditary symbol (who may be an emperor, king or queen, or prince) who mainly plays a representative role and performs civil but does not exercise executive or policy-making powers alone but executes in conjunction with the Prime Minister. Constitutional monarchs embody and represent the legitimate constitutional authority of the state. Their presence helps to reinforce the legitimacy of government actions.